The wake-up call - O'Leary, Beth (Berkley Romance, 2023)
"Two hotel receptionists--and archrivals--find a collection of old wedding rings and compete to return them to their owners, discovering their own love story along the way. It's the busiest season of the year, and Forest Manor Hotel is quite literally falling apart. So when Izzy and Lucas are given the same shift on the hotel's front desk, they have no choice but to put their differences aside and see it through. The hotel won't stay afloat beyond Christmas without some sort of miracle. But when Izzy returns a guest's lost wedding ring, the reward convinces management that this might be the way to fix everything. With four rings still sitting in the lost and found, the race is on for Izzy and Lucas to save their beloved hotel--and their jobs. As their bitter rivalry turns into something much more complicated, Izzy and Lucas begin to wonder if there's more at stake here than the hotel's future. Can the two of them make it through the season with their hearts intact?"--